Metodologičeskie voprosy obščestvennych nauk. Vyp. 2. Pod red. V.P. Tugarinova i A.V. Drozdova. [Pri učast. G.A. Podkorytova, G.G. Karavaeva, V.Ja. El'meeva i dr.] (Izd-vo leningradskogo un-ta, 1971)
Leningradskij gos. universitet im. A.A. Ždanova.